(untitled) (Research, Society and Development, 2022)
The World Health Organization (WHO) considers maternal death to be the death of a woman during the period of pregnancy, childbirth or puerperium, up to 42 days after the end of pregnancy, having as causes the complications related or arising from this period, excluding those of the accidental or incidental type. Objective: analysis of maternal mortality in Northeastern Brazil between 2010 and 2019, including variables such as education, place of occurrence, age and marital status. Methodology: This is a retrospective descriptive study with the objective of analyzing all reported cases of maternal death that occurred in Northeastern Brazil from 2010 to 2019. The variables analyzed were: maternal deaths, type obstetric cause, maternal subcategories, underlying cause ICD-10 group, age group, color/race, marital status, education and place ofoccurrence. The maternal mortality ratio (MMR) was calculated using the formula: number of deaths due to maternal causes, over the number of LB (live births) in the period X 100,000. Simple descriptive statistics were used for data analysis, which will be presented through graphs and tables. The programs used were Excel and Qgis. Data between 2010 and 2019 were included, and those that did not meet the analyzed sociodemographic criteria were excluded. Spatial analysis was performed using the free Qgis® software, applying quantile statistics. The shapefiles (maps) were collected from the IBGE database, and the maternal deaths obtained from each state in the Northeast region collected through SIM-DataSUS were added to the maps. Results: Through this study we obtained the following data: epidemiological profile of maternal deaths in the Northeast Region - age group from 20 to 29 years old (44.52%), schooling 8 to 11 years old (33.27%), mixed race (74, 25%), single (51.87%) and deaths in hospitals (98.91%). Conclusion: Maternal mortality is a topic that requires intensive care and attention so that there is enough theoretical basis to lead public policies directed to the topic and that bring about change in this scenario.